Boosting Accuracy and Fluency in Speaking Skills: An ARCS Model Intervention for Indonesian Tourism Students - Purwanto, Muhammad Bambang; Yuliasri, Issy; Widhiyanto; Rozi, Fahrur (Journal of Education Reseach and Evaluation, 2025)
The low speaking skills of students in the context of learning English for specific purposes, such as tourism, encourage the need for a more effective teaching approach. This study aims to analyze the ARCS Model's effectiveness in improving students' speaking accuracy and fluency in the tourism study program at Politeknik Negeri Sriwijaya. This study used a quasi experimental design with a pretest and posttest approach, involving 60 EFL students (22 males and 38 females) aged 18–20 years who took the English for Hospitality course in the second semester of the 2025 academic year. The homogeneity of the participants' initial abilities was tested using the Oxford Placement Test (OPT). The participants were randomly divided into an experimental group (with the ARCS Model) and a control group (with conventional methods). The instrument used was the Cambridge PET speaking test, with two assessment indicators: Error-Free Clauses per T-unit (EFC/T) for accuracy and Words per Minute (W/M) for fluency. Data analysis was done using MANOVA with the help of IBM SPSS Statistics software version 24.0. The results showed a statistically significant improvement in the experimental group for both aspects of speaking skills, with a significance value of p < 0.001, and a Partial Eta Squared effect size of 0.522 (accurate) and 0.805 (fluent). These findings concluded that the ARCS Model effectively improves speaking skills, especially fluency, compared to conventional teaching methods. Therefore, integrating the ARCS Model in the foreign language curriculum at vocational institutions is recommended to strengthen students' communicative competence and competitiveness in the global tourism industry.